Comparison of 30 meter sprint running times with and without finish line in male athletes - Turkeri, C.; Ozturk, D. (International Journal of Applied Exercise Physiology, 2020)
Sprint running is known with a general name of 60m, 100m, 200m and 400m short distance races. Sprint is one of the few motoric properties that can be improved. Athletes participating in these speed competitions are called sprinter. The aim of this study is to examine the 30m sprint running, with and without finish line of between the male athletes. A total of 94 male athletes were participated in this study as voluntarily. The mean age, weight, height, age of sport, age of starting sports, weekly training hours and BMI of the participants are 18.44 ± 1.60 years, 69.67 ± 10.10 kg, 177.98 ± 6.11 cm, 4.71 ± 3.18 years, 13,79 ± 2,94 years, 16.08 ± 4.36 hours, and 22.05 ± 2.82 kg/m2, respectively. In this study, Kolmogorov-Smirnov test was used to determine the distribution of normality of obtained data. The parametric tests were applied since the data have shown the normal distribution. Paired t test and ANOVA test were used to compare the differences between the mean values. According to the results, there was a significant difference between the athletes' age groups (p=0.03), weekly training hours (p=0.00), and 30m sprint running times with and without finish line (p=0.01). It is concluded that the results for the athletes running without finish line (4.15sec) are better than those of the athletes running with finish line (4.20sec). In addition, according to another finding in this study, it can be argued while age from adolescence to youth and the weekly training time increase, the speed increases.